Editorial: Unaccompanied Minors in Europe - Part II - Maren Zeller; Philipp Sandermann (Social Work and Society)
To this date, there is a lack of data on the absolute number of people who became refugees in 2017. There are reasons to assume, though, that the global situation regarding flight and migration has not changed significantly since we published Part I of this special issue on"Unaccompanied Minors in Europe" in the fall of 2017. However, there seem to be new trends with regard to refugees seeking asylum in the EU, generally, and concerning those young people who arrive and live in Europe under the label of being an unaccompanied minor (UAM). This applies to various constituents. For example, the refugee routes currently seem to be changing; the number of young people coming to Europe seems to be declining, policies are becoming more restrictive while at the same time formally putting forward the best interest of the child and, alongside this, the challenges for professionals dealing with UAM are obviously changing.